Violence and the medieval clergy - Jaritz, Gerhard; Marinković, Ana (Budapest ; New York : Central European University Press, 2011)
Violence was omnipresent in medieval society and affected all areas of life and the members of all social strata. Surviving sources deal regularly with any issues of violent actions, signs and results of violence, violent people and coping with violence. In such evidence, also the members of the clergy played an important role—as writers about violence and critics of it, but also as perpetrators, victims, and witnesses.
Papers from the workshop "Coping with violence, and the medieval clergy (from the local settlement of dispute to approaching the Papal Penitentiary)," held at Dubrovnik in 2008.
Includes bibliographical references and index.
Keywords: nasilje; srednji vijek; crkva; crkvena povijest; svećenstvo - -- redovnici